Comparative detection efficacy of primers targeting SpeI-AvaI restriction fragment and small subunit ribosomal RNA gene of Babesia bigemina - KAUR, PARAMJIT; JUYAL, PRAYAG DUTT; SHARMA, AMRITA; SINGLA, LACHHMAN DAS; MUKHOPADHYAY, CHANDRA SEKHAR (The Indian Journal of Animal Sciences, 2023)
The objective of the study is to evaluate the comparative detection efficacy of primers targeting SpeI-AvaI restriction fragment and small subunit ribosomal RNA (SSU rRNA) gene of Babesia bigemina by employing conventional polymerase chain reaction (PCR) on 783 animals (296 cattle and 487 buffaloes) of low lying (bet) area of Punjab. The detection rate of SpeI-AvaI and SSU rRNA PCR assays was 3.96% (31/783), and 6.64% (52/783), respectively. Among cattle and buffaloes, prevalence of B. bigemina was higher (P<0.01) in cattle by both the primers. The sensitivity and specificity of SSU rRNA PCR as compared to SpeI-AvaI restriction fragment PCR was 100% and 97.2%, respectively. The blast analysis of the nucleotides of the sequenced amplicons of Ludhiana isolates of SpeI-AvaI and SSU rRNA PCR assay of B. bigemina showed 83 and 100% similarity with available sequence in Genbank. The analysis of evolutionary divergence revealed that range of divergence was lying between 0.000 to 0.011 between SSU rRNA sequence with the other sequences of B. bigemina as well as Babesia species. To conclude, the primers targeting SSU rRNA gene are a better tool for amplification of the B. bigemina.